2018
DOI: 10.3390/f9110680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Layer and Plant–Soil Interaction on Soil Microbial Diversity and Function after Canopy Gap Disturbance

Abstract: Gaps by thinning can have different microclimatic environments compared to surrounding areas, depending on the size of the gap. In addition, gaps can play important roles in biological dynamics, nutrient cycling, and seedling regeneration. The impacts of gap size on soil microbial communities and enzyme activities in different soil layers in Chinese pine plantations are not well understood. Here, we created gaps of 45 m2 (small, G1), 100 m2 (medium, G2), and 190 m2 (large, G3) by thinning unhealthy trees in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…At each site, we divided a plot of 10 × 10 m from the area away from the road. We collected surface soil (0–15 cm) samples using five-point method and mixed into one soil sample at each plot [ 6 , 38 ]. Soil samples from all 50 sampling locations were filtered in sterilized stainless steel vessels to remove tree roots, rocks, plant, and animal debris with tweezers.…”
Section: Framework and Data Collectionmentioning
confidence: 99%
“…At each site, we divided a plot of 10 × 10 m from the area away from the road. We collected surface soil (0–15 cm) samples using five-point method and mixed into one soil sample at each plot [ 6 , 38 ]. Soil samples from all 50 sampling locations were filtered in sterilized stainless steel vessels to remove tree roots, rocks, plant, and animal debris with tweezers.…”
Section: Framework and Data Collectionmentioning
confidence: 99%
“…Mackay et al and Smith et al also found this phenomenon in mixed-species forests [14,48]; Yang et al found that total PLFA abundance significantly changed only in the first 2 or 4 years in artificially planted Sonneratia apetala and Sonneratia caseolaris stands, pointing out that microbial biomass might have reached a stable state in the first few years [49]. AMF plays an important role in improving soil fertility [12,50], and Luo et al found the highest amounts of AMF in the oldest Picea asperata plantations (50-year) [51]. Interestingly, AMF abundances were significantly highest in 25-year stands and then decreased in 45-year ones in our study, probably because young trees have more developed fine roots than older trees [52,53].…”
Section: Effect Of Stand Age On Microbial Communities and Enzyme Actimentioning
confidence: 89%
“…Furthermore, soil microorganisms and extracellular enzymes excreted by microbes are also useful indicators given their important roles in nutrients conversion and organic matter decomposition [11]. Changes in microbial communities or enzyme activities can reflect shifts in soil fertility [12][13][14]. To assess soil fertility more comprehensively, soil physicochemical and microbial parameters should be synthesized in studies while in recent years, more efforts have been made towards exploring soil physicochemical properties of Chinese fir plantations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…All the sampling sites were paddy fields and all the paddies from the sampling sites were xiushui 134. The soil samples were collected from the bulk topsoil (0–10 cm) along a 100 × 100 m square (Legrand et al, 2018; Yu et al, 2018). Samples were removed of roots, stones, plant residues, animals and other things manually, then stored with 20 g per sample below −80 °C before DNA extraction, and transported 500 g per sample to the laboratory for analysis on physicochemical, heavy metals and other environmental variables (Lüneberg et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Soil microbial communities play a critical role in organic matter (OM) decomposition and nutrient cycling of carbon, nitrogen and phosphorus. They could respond quickly to the environmental changes (Bender, Wagg & Van Der Heijden, 2016; Nottingham et al, 2018; Yu et al, 2018). The diversity and composition of the soil microbial community is directly related to its function, structure and aggregation (Bender, Wagg & Van Der Heijden, 2016; Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%